Reestablishment of sperm quality after long-term deslorelin suppression in tomcats - Nuñez Favre, Romina de Los Angeles (2018)
The aim of the study was to determine the time after treatment with a 4.7 mg deslorelin implant until Tomcat spermatogenesis activity was restored, and seminal parameters reached pre-implant values. Tomcats (n = 6) were randomly assigned to one of two treatments. Three cats (n = 3) received a deslorelin implant (4.7 mG; Suprelorin®, Virbac, France) in the interscapular subcutaneous region whereas three (n = 3) received no implant and served as control group. Semen samples were collected by electroejaculation every 4 wk from 3 mo before treatment (pretreatment samples) until reestablishment of pre-treatment sperm quality, 32 mo post-implant insertion (PI). Each semen sample was assessed for motility, velocity, concentration, total sperm count, viability, acrosome integrity, plasma membrane integrity and sperm morphology. After semen collection, testicular volume and presence/absence of penile spines were recorded. Additionally, blood samples were taken to measure testosterone concentration. An increase in sperm concentration and total sperm count was present 1 mo PI despite of an abrupt decrease in serum testosterone concentrations after 2–4 weeks. This initial stimulatory effect was followed by a decrease in seminal parameters, reduction of testicular volume and disappearance of penile spines 2 mo PI. A single Suprelorin® 4.7 mg implant suppressed sperm production for 22–25 months. No clinically side effect was observed during the study period. All toms returned to their initial seminal quality 23–28 months after treatment. Therefore, we conclude that Suprelorin® 4.7 mg is a safe option for reversible reproduction control during long periods in tomcats.